Escenario técnico y económico para la valorización integral a pequeña escala de residuos de naranja en Colombia - Bedoya Betancur, Santiago; Amar Gil, Sebastian; Barrera Z., Rolando; Arriola V., Erasmo; Ardila A., Alba N. (Ingeniería, 2022)
Context: The integral valuation of orange peel was studied under a biorefinery scheme where orange oil (with hydrolate as a by-product and the valorization of the oil through the extraction of limonene in later stages), pectin and flour were obtained for use as a supplement in animal feeding. Method: The process consisted of four general stages: i) extracting and obtaining orange oil and hydrolate through steam distillation, ii) obtaining limonene, iii) extracting pectin through the acid hydrolysis method, and iv) obtaining animal food from centrifugation and drying processes. Results: The experiments and characterizations were carried out at the laboratory scale, from 700 g of peel (wet) 3,34 mL of oil (80-85 % limonene), about 500 mL of hydrolate and about 260 g of solid residues (dry) were obtained. From these, around 9,7 g of pectin and around 40,3 g of flour for animal food supplements were obtained from batches of 50 g of dry material. Conclusions: According to the technical-economic analysis for the scale of production used, as well as for the national context, positive indicators such as the net present value (27’271.933) and the internal rate of return (5,27 %) were achieved, which show an interesting investment alternative to be considered as a waste valorization option for small and medium citrus producers in the country.